Analisis Kasus Pelecehan Seksual Di Universitas Islam Indonesia Menggunakan Pendekatan Hak Asasi Manusia - Diana Farid; Kemal Al Kautsar Mabruri Mabruri; Muhammad Husni Abdulah Pakarti; Hendriana Hendriana (Scholar Center, 2023)
Human rights that must be upheld and respected by each citizen for the sake of honor and protection of human dignity. However, human rights violations still occur frequently, as reflected in the persistence of sexual violence experienced by women. Likewise, Ibrahim Malik (IM) took advantage of his popularity and good image as an Outstanding Student (mapres) to attract victims. The purpose of this research is to find out how the sexual harassment case committed by IM began, the actions taken by the victim, and then the response from the Indonesian Islamic University (UII) where IM studied about the case. The method used in this paper uses secondary data as a bibliography, with data analysis used in a qualitative descriptive manner. The results of the temporary research show that IM received sanctions for his actions by revoking the title of outstanding student from the Islamic University of Indonesia because he had violated the ethics and morals of being an outstanding student. It started with a complaint from one of the victims to the Yogyakarta Legal Entity Institute on April 17, 2020, followed by complaints from other victims who told similar incidents, where the incident occurred in 2016. Until May 4, 2020, there were 30 complainants out of 30 people who reported sexual harassment by the same perpetrator, IM. The owner of the Twitter account @lnddwrhy stated that the hope of the victims through the Yogyakarta Legal Aid Institute regarding this case, if summarized, was for UII to make regulations related to the prevention and handling of cases of sexual violence on campus so that similar cases would not occur again because the alma mater of the majority of victims came from the same campus as IM, there is also no longer a group of people who provide a stage for IM in the form of glorification, including at UII where IM is pursuing a bachelor's degree